Analysis of presentation, etiology, management and outcome of perforation peritonitis in a tertiary care centre - Kumari, Shweta; Kumar, Ajay; Ranjan, Alok; Thakur, Indra Shekhar (International Journal of Research in Medical Sciences, 2023)
Background: The most common surgical emergency in general surgery is perforation peritonitis. It is a serious condition with a mortality rate of up to 20%, and it is the third most common cause of surgical abdomen after appendicitis and intestinal obstruction. The aim of this study to discuss presentation, etiology, management and outcome of perforation peritonitis in our hospital. Methods: The 60 patients with features of perforation peritonitis admitted from September 2021 to August 2022 in the department of general surgery, PMCH, Patna were chosen. Descriptive statistics was used for analysis. Detailed history was taken, physical examination and X-ray was done. Signs and symptoms, duration of illness, age of presentation, intra-op findings regarding size and location, its management, post-op complications were documented. Results: Total 60 cases of perforation peritonitis were included in this study, among that 80% (48) were males and 20% (12) were females, with male to female ratio of 4:1. Pain abdomen was a universal symptom. Generalized pain abdomen was seen in 54 (90%) cases, followed by lower quadrant in 3 cases (5%) and epigastrium pain seen in 3 cases (5%). Radiation of pain to right iliac fossa was seen in 6 cases (10%). Blunt injury was seen in 9 (15%) case. 14 patients were treated with anti-ulcer medications. Three patients with duodenal ulcer perforation were treated with nonsteroidal anti-inflammatory drugs. Liver dullness was obliterated in 28 patients (47%). Bowel sounds were either sluggish or absent in most cases. Conclusions: Perforation peritonitis is a frequently encountered surgical emergency. Various factors like age, sex, duration, site of perforation, extent of peritonitis and delay in surgical intervention are associated with morbidity and mortality. A successful management depends upon early surgical intervention, source control and exclusive intraoperative peritoneal lavage.